Analisis Pengelolaan Kurikulum Untuk Meningkatkan Kualitas Pendidikan - Alifah Aulia Nurfadhilah; Daffa Harits Ariyadi; Dwi Ratnawati; Erva Karimatunisa; Kurnia Dewi Kusumaningrum; Bahtiyar Heru Susanto (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research aims to analyze curriculum management as an effort to improve the quality of education. The curriculum is an important component in the education system that determines the direction, content and methods of learning. Through effective management, the curriculum can be prepared and implemented well so that it is able to support the achievement of the expected graduate competencies. The research method used in this research is a qualitative method with a literature study approach. This approach was chosen because it allows researchers to thoroughly analyze various sources of information and relevant literature on curriculum management. Therefore, this research suggests the need to increase school management capacity and provide adequate resources to support an effective curriculum.